Nilai Perusahaan dan Perencanaan Pajak: Systematic Literature Review dengan Obyek Penelitian pada Perusahaan Terbuka Sektor Konsumsi di Indonesia - Stefanie Febrianti Andreas; Nugroho Wisnu Murti; Saptani Rahayu (STIE AUB Surakarta, 2026)
This article synthesizes 15 empirical studies to identify research gaps on the relationship between tax planning and firm value in the Indonesian consumer staples sector. The synthesis reveals that only two articles explicitly examine the direct effect of tax planning on firm value. Yielding contradictory results (negative significant vs positive significant moderated by transparency), thus no consistent pattern is found. Most articles position tax planning merely as a control variable, while profitability emerges as the most dominant and consistently positive determinant. Consequently, this study identifies several contextual variables that should be considered in future research, including leverage, capital structure, liquidity, solvability, firm size, investment decisions, and managerial ownership. The dominant theoretical foundations are Signaling Theory and Agency Theory, opening opportunities for further studies to develop more integrated models that incorporate these contextual variables through model development, sector expansion, or theoretical integration